Importance of different accounting costing methods for cutting costs of Bata Bangladesh footwear production, retail stores and warehouses - Ahmed, Rafi (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.